2011
DOI: 10.4254/wjh.v3.i6.157
|View full text |Cite
|
Sign up to set email alerts
|

MELD score, insulin-like growth factor 1 and cytokines on bone density in end-stage liver disease

Abstract: Osteopenia/osteoporosis is common in advanced liver disease. Low serum IGF-1 is weakly predictive but serum cytokine and MELD score fail to predict the severity of bone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…In accordance with our findings, another recent study by Mitchell et al failed to detect an association between serum cytokines IL-6 and TNF α and bone mineral density or bone turnover and levels of IL-6 and TNF did not differ between those with and without reduced bone density [ 24 ]. However, they found that low body mass index (BMI), increased bone turnover, and low IGF-1 were independent predictors of low spinal bone density.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our findings, another recent study by Mitchell et al failed to detect an association between serum cytokines IL-6 and TNF α and bone mineral density or bone turnover and levels of IL-6 and TNF did not differ between those with and without reduced bone density [ 24 ]. However, they found that low body mass index (BMI), increased bone turnover, and low IGF-1 were independent predictors of low spinal bone density.…”
Section: Discussionsupporting
confidence: 92%
“…On a molecular level, low-turnover osteoporosis in CLD patients is commonly associated with toxic effects of biliary stasis and copper/iron accumulation on differentiation, maturation, and proliferation of osteoblasts (Figure 3 )[ 68 - 70 ]. Also, previous studies suggested that osteoblast dysfunction in patients with cholestatic forms of CLD could be mediated by insulin growth factor-1 or oncofetal fibronectin[ 66 , 70 , 71 ], while direct toxic effects of alcohol on osteoblastic function contribute to bone loss among patients within alcohol-induced CLD[ 72 , 73 ].…”
Section: The Molecular Mechanisms Involved In Etiopathogenesis Of Cld...mentioning
confidence: 99%
“…insulin like growth factor 1, IGF-1) ili onkofetalni fibronektin (engl. oncofetal fibronectin), ali i posledica toksičnog efekta staze bilirubina i žučnih kiselina koja može biti prisutna kod pacijenata sa alkoholnom cirozom jetre (slika 3) (56)(57)(58). Uz to, nedavno je objavljeno da povećana koncentracija sklerostina, kao ključnog regulatora Wnt/ß-katenin signalnog puta koji reguliše stvaranje kostiju, može biti uključena u patogenezu osteoporoze kod ACJ pacijenata (42,59).…”
Section: Mineralna Gustina Kostiju U Alkoholnoj Cirozi Jetreunclassified